Why Socio-Economic Inequalities in Health Threaten Relational Justice. A Proposal for an Instrumental Evaluation. (5th November 2018) - Haverkamp, Beatrijs; Verweij, Marcel; Stronks, Karien
Abstract: In this article, we argue that apart from evaluating the causes and the social determinants of health inequalities, an evaluation of the effects of health inequalities is due. For this, we propose the ideal of relational equality as an evaluative framework, and test to what extent health inequalities threaten this ideal of a society of equals. We identify three ways in which they do (i.e. via unequal risks to stigmatization, unequal risks to unemployment and unequal risks to unequal pension enjoyments) and argue that these risks are especially great for those lower down the socio-economic strata. We thus conclude that equality in health is instrumental to social justice, and that socio-economic inequalities in health are not only unjust due to their causes but also due to their consequences. We continue to argue that our instrumental approach opens a perspective to mitigate the identified injustices by changing society, rather than reducing inequalities in health, and argue that this is an advantage in the light of the realistic assumption that (part) of the socio-economic health inequalities will persist. The article thus offers a complementary approach to both the evaluation and the mitigation of the injustice of socio-economic inequalities in health.